Prevalence and Factors Associated With Cancer‐Related Fatigue Among Children and Adolescents Undergoing Cancer Treatment: A Systematic Review and Meta‐Analysis - Sapna Oberoi; Beili Huang; Rasheda Rabbani; Nicole Askin; George Okoli; Richa Jain; Lillian Sung; Maya M. Jeyaraman; Alyson Mahar; Roberta Woodgate; Ryan Zarychanski (Cancer Medicine)
ABSTRACT Background The literature on fatigue in children and adolescents undergoing cancer treatment is highly variable, creating uncertainties about its prevalence and identifying those at higher risk. Objectives The primary purpose was to describe the prevalence of fatigue among patients (< 21 years) undergoing cancer treatment across cancer types. Secondary outcomes included the prevalence of severe fatigue and factors associated with fatigue. Methods Systematic searches of MEDLINE, Embase, Cochrane Central Register of Controlled Trials, CINAHL, and PsycINFO were conducted from inception to May 22, 2023. Two reviewers independently identified relevant citations and extracted data. Pooled prevalence estimates were derived using an inverse variance, random‐effects model. We used Joanna Briggs's critical appraisal checklist to assess study quality. (PROSPERO: CRD42020179307). Results We included 47 studies: 26 for prevalence and 29 for factors associated with fatigue. The pooled prevalence of fatigue was 73% (95% [Confidence Interval, CI: 66%–79%; I2 96%; 26 studies; 2699 patients], and severe fatigue was 30% [95% CI 14%–46%, I2 98%; 8 studies; 1027 patients]). Subgroup analyses based on cancer type, study design, fatigue scale, fatigue reporting personnel, sample frame, and response rate did not reveal significant differences in fatigue prevalence. Fatigue prevalence significantly differed by treatment setting (inpatient [83%] vs. outpatient [55%] vs. inpatient and outpatient [69%]; p: 0.02). Due to considerable heterogeneity among studies, data on fatigue‐associated factors are presented descriptively. Conclusions The prevalence of fatigue among children and adolescents undergoing cancer treatment is variable but notably high. Systematic evaluation of factors associated with fatigue is essential to understanding which children are at high risk of developing fatigue. Trial Registration PROSPERO: CRD42020179307